Electrophysiological and neuromuscular stability of persons with chronic inflammatory demyelinating polyneuropathy. Issue 3 (23rd March 2017) - Gilmore, Kevin J.; Allen, Matti D.; Doherty, Timothy J.; Kimpinski, Kurt; Rice, Charles L.
ABSTRACT: Introduction: We assessed motor unit (MU) properties and neuromuscular stability in the tibialis anterior (TA) of chronic inflammatory demyelinating polyneuropathy (CIDP) patients using decomposition‐based quantitative electromyography. Methods: Dorsiflexion strength was assessed, and surface and concentric needle electromyography were sampled from the TA. Estimates of MU numbers were derived using decomposition‐based quantitative electromyography and spike‐triggered averaging. Neuromuscular transmission stability was assessed from concentric needle‐detected MU potentials. Results: CIDP patients had 43% lower compound muscle action potential amplitude than controls, and despite near‐maximum voluntary activation, were 37% weaker. CIDP had 27% fewer functioning MUs in the TA, and had 90% and 44% higher jiggle and jitter values, respectively compared with controls. Conclusions: CIDP had lower strength and compound muscle action potential values, moderately fewer numbers of MUs, and significant neuromuscular instability compared with controls. Thus, in addition to muscle atrophy, voluntary weakness is also due to limitations of peripheral neural transmission consistent with demyelination. Muscle Nerve 56 : 413–420, 2017